Comparative indicators of morphology and seed productivity in rare Iris L. spp. within their natural habitats and under cultivation in the Southern Urals - A. V. Kryukova; A. N. Mustafina; L. M. Abramova (Труды по прикладной ботанике, генетике и селекции)
Background. Wild irises are promising for cultivation and use in breeding practice. Many of them are included in Red Lists, as they disappear under the impact of anthropogenic factors. It is biologically important to study their morphometric and reproductive parameters, so that the most stable and highly ornamental species could be recommended for expanding the range of flower plants.Materials and methods. Biological features of four Iris L. species rarely occurring in the Southern Urals: I. pseudacorus L., I. pumila L., I. scariosa Wild. ex Link, and I. humilis Georgi, were studied in 2012–2017 in 23 natural and 4 introduced cenopopulations. Individual parameters were compared for 25 medium-age plants from each cenopopulation in their mass-flowering and fruiting phase according to 11 biometric parameters using conventional methods. Statistical significance of the differences was assessed using Student’s t-test.Results. Comparison of morphometric parameters of four rare Iris spp. naturally occurring and introduced in Bashkortostan during six years of research showed significant differences between cenopopulations at a 5% significance level for most traits of I. pumila and I. pseudacorus. As for I. scariosa and I. humilis, differences were mostly insignificant (at tfact< 2.064). Mean values of most reproductive parameters for I. scariosa, I. humilis and I. pseudacorus were significantly lower under introduction conditions than in natural populations. Under cultivation, seed productivity of I. pumila increased. Variability of most morphometric features of the studied irises was within normal response limits for the studied species. When cultivated in the environments of the Bashkir Cis-Urals, they bloom and bear fruit every year, except for I. humilis.Conclusion. Of the four rare Iris spp., I. pumila is recommended for landscaping settlements in the South Urals as the most stable species.